Aconicumines A–D, an advanced class of norditerpenoid alkaloids with an unprecedented N, O-diacetal motif from Aconitum taipeicum Hand.-Mazz., exhibit anti-inflammatory properties in vitro. (June 2023) - Zhang, Dong-Bo; Liang, Yan-Ni; Wang, Zheng; Shi, Li-Ke; Zhang, Zhen; Tang, Zhi-Shu; Huang, Lu-Qi
Abstract: Aconicumines A–D, an advanced class of norditerpenoid alkaloids, and seven known alkaloids, were isolated from Aconitum taipaicum Hand.-Mazz. (Ranunculaceae). The structures of the previously undescribed compounds, including their absolute configurations, were fully elucidated based on spectroscopic and single-crystal X-ray diffraction data analysis. Aconicumines A–D exhibit interesting cage-like structure, characterised by an unprecedented N, O- diacetal moiety (C6–O–C19–N–C17–O–C7) that has not been previously observed in diterpenoid alkaloids. Possible biosynthetic pathways for aconicumines A–D were proposed. Aconitine, hypaconitine, and aconicumine A showed significant inhibition of nitric oxide production in RAW 264.7 macrophages induced by lipopolysaccharide with IC50 values ranging from 4.1 to 19.7 μM compared to positive control (dexamethasone, IC50  = 12.5 μM). Furthermore, the primary structure–activity relationships for aconicumines A–D were also represented. Graphical abstract: Image 1 Highlights: Four undescribed diterpenoid alkaloids (DAs) were isolated from Aconitum taipaicum. All structures with their absolute configurations were completely determined. Aconicumines A–D possessed rare 7, 17-seco-DAs carbon skeleton in natural. Aconicumines A–D presented an unprecedented N, O -diacetal residue in DAs. Aconicumine A showed significant (nitric oxide) NO inhibitory activity.